TRANSITION FROM TRADITIONAL TEACHING METHODS TO AN INNOVATIVE ECOSYSTEM IN THE EDUCATION SYSTEM - Eshmanov , G‘afur (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article examines the theoretical and practical foundations of the transformational processes occurring in the modern educational system—the transition from traditional teaching methods to an innovative digital ecosystem. The author analyzes the necessity of a paradigm shift in education, specifically the evolution from an "instructor-centered" system to a "learner-centered" technological environment. The role of artificial intelligence, cloud technologies, and hybrid learning models in enhancing the efficiency of the educational process is highlighted. Furthermore, the article addresses the pedagogical and technical challenges encountered in the formation of a digital ecosystem and proposes scientific solutions to overcome these obstacles.